Search for long-lived particles decaying to e± μ∓ ν - Aaij, Roel; Archilli, Flavio; Berninghoff, Daniel; Frau, Giulia; Grabowski, Jascha; Han, Xiaoxue; Hu, Jiangqiao; Leverington, Blake; Malygina, Hanna; Stemmle, Simon; Uwer, Ulrich; Witola, Lukas (The European physical journal. C, Particles and fields, 2021)
Long-lived particles decaying to $${e ^± } {μ ^\mp } {ν } $$, with masses between 7 and $$50 \,\text {GeV/}c^2 $$and lifetimes between 2 and $$50 \,\text {ps} $$, are searched for by looking at displaced vertices containing electrons and muons of opposite charges. The search is performed using $$5.4 \,\text {fb} ^{-1} $$of